2014
DOI: 10.1002/dvg.22754
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive survey of wnt and frizzled expression in the sea urchin Paracentrotuslividus

Abstract: Summary: WNT signaling is, in all multicellular animals, an essential intercellular communication pathway that is critical for shaping the embryo. At the molecular level, WNT signals can be transmitted by several transduction cascades, all activated chiefly by the binding of WNT ligands to receptors of the FRIZZLED family. The first step in assessing the biological functions of WNT signaling during embryogenesis is thus the establishment of the spatiotemporal expression profiles of wnt and frizzled genes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 44 publications
6
59
1
Order By: Relevance
“…S2 and S3. Similar results have been established in the embryos of a related species of sea urchin, Paracentrotus lividus (21). Because this study focuses on identifying the function of Wnt signaling in the interaction between different cell-fate specification processes, we have represented individual gene-expression patterns abstractly according to their embryonic expression domain (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…S2 and S3. Similar results have been established in the embryos of a related species of sea urchin, Paracentrotus lividus (21). Because this study focuses on identifying the function of Wnt signaling in the interaction between different cell-fate specification processes, we have represented individual gene-expression patterns abstractly according to their embryonic expression domain (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Phylogenetic analysis of X. bocki Wnt relatives was performed as explained previously [29], using a maximum-likelihood approach with the program RAxML and 100 bootstrap replications. The alignment of the reference species was provided by Dr J. C. Croce [80] and included the sequences from the species Pl, Lg, Hs and Xt (see below for abbreviations); the other sequences are used in Kusserow et al [81] and were downloaded from the NCBI database, the accession numbers are indicated after the name. Protein families are highlighted in different colours.…”
Section: A Genomics View Of Xenacoelomorpha Neurogenesismentioning
confidence: 99%
“…Four Frizzled receptor genes have been identified so far in the Strongylocentrotus purpuratus genome but no information is available about the expression dynamics of these genes during embryogenesis. The expression of these receptors has been deeply investigated in another sea urchin species, Paracentrotus lividus, indicating Fzd9/10 as possible candidate for mediating Wnt10 signaling in the hindgut (Croce et al, 2006;Lhomond et al, 2012;Robert et al, 2014). It would be interesting to study the dynamics of expression of the four Frizzled receptor genes in S. purpuratus in order to identify a possible candidate for the transduction of the Wnt10 signal to the intestinal cells.…”
Section: Conserved Function and Regulation In Intestine Differentmentioning
confidence: 99%